Does Probability Guided Hysteroscopy Reduce Costs in Women Investigated for Postmenopausal Bleeding? - M. C. Breijer; N. van Hanegem; N. C. M. Visser; R. H. M. Verheijen; B. W. J. Mol; J. M. A. Pijnenborg; B. C. Opmeer; A. Timmermans (The Scientific World Journal)
Objective. To evaluate whether a model to predict a failed endometrial biopsy in women with postmenopausal bleeding (PMB) and a thickened endometrium can reduce costs without compromising diagnostic accuracy. Design, Setting, and Population. Model based cost-minimization analysis. Methods. A decision analytic model was designed to compare two diagnostic strategies for women with PMB: (I) attempting office endometrial biopsy and performing outpatient hysteroscopy after failed biopsy and (II) predicted probability of a failed endometrial biopsy based on patient characteristics to guide the decision for endometrial biopsy or immediate hysteroscopy. Robustness of assumptions regarding costs was evaluated in sensitivity analyses. Main Outcome Measures. Costs for the different strategies. Results. At different cut-offs for the predicted probability of failure of an endometrial biopsy, strategy I was generally less expensive than strategy II. The costs for strategy I were always € 460; the costs for strategy II varied between € 457 and € 475. At a 65% cut-off, a possible saving of € 3 per woman could be achieved. Conclusions. Individualizing the decision to perform an endometrial biopsy or immediate hysteroscopy in women presenting with postmenopausal bleeding based on patient characteristics does not increase the efficiency of the diagnostic work-up.